Digital Literacy Competencies of Students in Bandung - O Solihin; Y Mogot (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2021)
This study aims to determine the digital literacy competence of students in the city of Bandung. This study used descriptive qualitative method. The data collection technique used was semi-structured interviews involving 10 informants from 5 universities in the city of Bandung. The results showed that some students in the city of Bandung generally have digital literacy competencies which consist of: 1) the ability to understand internet searching, namely using search engines to find information, understanding the internet as a source of information, connecting and using the internet to carry out several activities; 2) competence in how hyperlinks work, even though they lack the meaning of hypertext; 3) content evaluation competence, they are able to understand the characteristics of websites that are used as references, cross-check the information they get and use FAQs on a website to help them get information; 4) competence in compiling knowledge by using keywords to facilitate the search for information, utilizing other sources of information other than the internet